Optimal moment to change pressure regulator and sprayer kit on center pivot irrigation machines: application to a study case - Leira, Ramón Pérez (2011)
A theoretical model developed by the authors for determining the optimal moment to substitute sprayer and pressure regulator kit on a center pivot irrigating potatoes and beans has been applied. The methodology compares the sum of the costs due to additional consumption of water and energy, maintenance and labor, as well as yield losses associated to areas with deficit or over irrigation to the costs due to buy and install a new sprinkling set on the pivot. The results showed that for a reduction of 3.07% of the Hermann and Hein’s Uniformity Coefficient (UCh), the substitution of the sprinkling module on the pivot is justified when potatoes and beans are cultivated.